Physical Simulation Experiment Study on Injection-Production Characteristics of Off-Surface Reservoirs in Sapu Oil Layer in Xing-6 Area - Liu, Ruhao; Wang, Xinrui; He, Xin; Song, Baoyu (Frontiers in Physics, 2022)
Based on the information of dense cored wells, and by analyzing off-surface reservoir data, determine the type of off-surface reservoirs in the area, the characteristics of off-surface reservoir microfacies (vertical), the planar distribution characteristics of off-surface reservoirs, and the off-surface reservoir rocks. Facies features, etc., so as to extract the matching pattern of the well pattern and the sand body. Based on the core analysis of the cored well area and the analysis of the matching relationship between injection and production between wells, five typical conventional off-surface and high-quality strip sand body injection and production modes between wells were extracted, and five corresponding core physical models and numerical models were constructed; Through physical simulation displacement experiment and numerical simulation displacement experiment analysis, the research shows that: conventional off-surface reservoirs can be exploited separately and can be produced well, with a recovery rate of 40%; conventional off-surface reservoirs are combined with high-quality strip sand bodies. Under mining conditions, there is serious interlayer interference; under the condition of tandem mining of conventional off-surface reservoirs and high-quality strip sand bodies, the production level of off-surface reservoirs can be effectively improved. Experiments show that the contribution rate of conventional off-surface reservoirs reaches 62% under the conditions of pin-out mining with high-quality sand bodies. The research results lay the foundation for further refined development and improvement of the economic and effective utilization of reserves.